2023
DOI: 10.1021/acsanm.2c04468
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Z-Scheme TiO2/Au/CdS Nanostructured Coating with Enhanced Photocathodic Protection Performance for Carbon Steel

Abstract: Photocathodic protection technology has presented great potential for protecting stainless steel; however, due to the higher electrochemical activity and more negative corrosion potential of carbon steel, most of them are not applicable to carbon steel. This study has fabricated a series of TiO2/Au/CdS nanostructured coating. The prepared samples have extended light absorbance to the visible light region. Among then, the TiO2/Au10/CdS nanostructured coatings have successfully offered cathodic protection to car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…The crystal structure of the different samples was determined by XRD. As shown in Figure a, it is clear that TiO 2 has an anatase structure, which is in perfect agreement with the JCPDS 21-1272 card . Although different templating agents were used, as can be seen in Figure b,c, the samples have different appearances, but the diffraction peaks of both CD and CE correspond to the hexagonal crystalline CdS card (JCPDS 41-1049) with a consistent crystalline shape .…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The crystal structure of the different samples was determined by XRD. As shown in Figure a, it is clear that TiO 2 has an anatase structure, which is in perfect agreement with the JCPDS 21-1272 card . Although different templating agents were used, as can be seen in Figure b,c, the samples have different appearances, but the diffraction peaks of both CD and CE correspond to the hexagonal crystalline CdS card (JCPDS 41-1049) with a consistent crystalline shape .…”
Section: Resultssupporting
confidence: 77%
“…As shown in Figure 1a, it is clear that TiO 2 has an anatase structure, which is in perfect agreement with the JCPDS 21-1272 card. 44 Although different templating agents were used, as can be seen in Figure 2b,c, the samples have different appearances, but the diffraction peaks of both CD and CE correspond to the hexagonal crystalline CdS card (JCPDS 41-1049) with a consistent crystalline shape. 45 In both the TCD and TCE samples, the TCD exposed a more pronounced (101) crystalline surface of anatase TiO 2 , indicating that there is no encapsulation of TiO 2 by CdS in this material and no formation of a core−shell structure as seen in the SEM image (Figure S1d).…”
Section: Characterization Of Materialsmentioning
confidence: 99%
“…(G) Electron-transfer mechanism of the TiO 2 /Au/CdS Z-scheme heterojunction coating. Reproduced with permission from ref . Copyright 2023 American Chemical Society.…”
Section: Tio2-based Heterojunction Coatingsmentioning
confidence: 99%
“…Graphene serves as an electron mediator, facilitating the migration of photogenerated e − from TiO 2 to g-C 3 N 4 . Xu et al 113 constructed TiO 2 /Au/CdS heterojunction coatings using the SILAR and ion-sputtering methods. The results indicated that the TiO 2 / Au/CdS heterojunction coating exhibited a maximum OCP drop of −0.591 V (Figure 13A), the photocurrent density was about 4 times that of TiO 2 (Figure 13B), and the chargetransfer resistance (R ct ) was reduced by about 9 times compared to TiO 2 (Figure 13C).…”
Section: All-solid-state Z-scheme Heterojunctionmentioning
confidence: 99%